Cortical predictors and correlates of cochlear implant outcome: a longitudinal study using functional near-infrared spectroscopy - Anderson, Carly Ann (2016)
While cochlear implants (CIs) have transformed the lives of hundreds of thousands of profoundly deaf individuals worldwide, the ability of individual patients to understand speech through their CI varies widely. The longitudinal study reported in this thesis aimed to investigate the role of cortical function and plasticity in helping to predict and explain variability in individual CI outcome.